Efficacy of iron treatments on hemoglobin and ferritin levels in iron deficient pregnant women: Systematic review and meta-analysis - J.P. Akshay Kirthan; Manjunath S. Somannavar; Noel George (Elsevier, 2023)
Objective: To compare the effectiveness of oral iron and intravenous iron therapy on the hemoglobin and ferritin levels in pregnant women with iron deficiency anemia. Method: Using PubMed, ProQuest and Google Scholar data-base, literature search was carried out and RCT studies comparing Oral vs IV iron in pregnancy published between 2012 and 2022 was selected. Use of intramuscular iron than Intravenous iron, studies comparing two IV and two Oral therapies, studies where only postpartum women received iron treatment were excluded. The risk of bias was assessed by using Cochrane Handbook for Systematic Reviews of Interventions. Data were combine to pooled mean difference and 95% confidence interval using random effects model. Results: 17 Articles were analyzed and included in the systematic review; all 17 were included in the meta-analysis for the hemoglobin, and nine were included for the ferritin. The hemoglobin and ferritin level increase after four weeks of treatment was statistically significant (p < 0.001). Cumulative results for both parameters indicate that there is little difference between the two groups, although both groups demonstrated positive effects. The pooled mean difference with 95% CI of hemoglobin and ferritin levels between the two groups was 1.01 [0.76, 1.26] and 58.84 [36.67, 81.00], respectively. Conclusions: In the meta-analysis, we found that intravenous iron is as effective as oral iron for treating iron deficiency anemia in pregnancy if only the increase in hemoglobin and ferritin is considered.